2017
DOI: 10.4103/ejd.ejd_160_17
|View full text |Cite
|
Sign up to set email alerts
|

Tooth extraction: Pattern and etiology from extreme Northwestern Nigeria

Abstract: Objective:Tooth extraction is a commonly performed procedure in dental clinics. It has been shown that the reasons for and pattern of tooth extraction vary across geographical regions. Few reports on the pattern of extraction among a semi-urban populace exist. To the best of our knowledge, there is no study on the pattern and reasons for tooth mortality from Sokoto, Northwestern Nigeria, which is a semi-urban region.Materials and Methods:A review of the records of patients that had tooth extraction at our cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
2
19
0
6
Order By: Relevance
“…The results of the Oral Surgery OPD of KMDC revealed that extractions and impaction were greater in 2018. (19) Hence it has been revealed that the tooth extraction is common procedure across the globe and major reasons of tooth loss were dental caries and periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the Oral Surgery OPD of KMDC revealed that extractions and impaction were greater in 2018. (19) Hence it has been revealed that the tooth extraction is common procedure across the globe and major reasons of tooth loss were dental caries and periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Pericoronitis treatment is dependent on the severity of infection and recurrence whereby options include antibiotics prescription, operculotomy, and extraction if the infection is recurrent. 15 It was also obvious that nonclinical or social factors still influence prescribing as shown by the case of the son of an elderly patient with diabetes and stents who requested a metronidazole prescription from the dentist. The dentist was willing to write a prescription without physically examining the patient and was consulting the colleagues regarding whether amoxicillin should be alternatively prescribed.…”
Section: Discussionmentioning
confidence: 99%
“…Degree of urbanization has also been found to affect the pattern of tooth extractions. (Taiwo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%